DIAGNOSTIC EVALUATION OF EXTRAPULMONARY TUBERCULOSIS: A COMPARATIVE STUDY OF FNAC, ZN STAINING, AND CB-NAAT TECHNIQUES - KUMARI, PRIYA; MISHRA, PRAGNYA PARAMITA; C., VISHWANATH (International Journal of Current Pharmaceutical Research, 2026)
Objective: To evaluate and compare the diagnostic efficacy of Fine Needle Aspiration Cytology (FNAC), Ziehl–Neelsen (ZN) staining, and Cartridge-Based Nucleic Acid Amplification Test (CBNAAT) in the diagnosis of extrapulmonary tuberculosis (EPTB). Methods: A prospective observational study was conducted on clinically suspected EPTB cases. FNAC smears were examined cytologically, ZN staining was performed for acid-fast bacilli, and CBNAAT was used for molecular detection of Mycobacterium tuberculosis and rifampicin resistance. Results: FNAC showed high sensitivity and rapid diagnostic utility, especially in resource-limited settings. ZN staining demonstrated very high sensitivity and strong rule-out value, but lower specificity. CBNAAT exhibited the highest specificity and reliably identified rifampicin resistance, making it the most effective confirmatory test. Higher EPTB incidence was observed among females. Conclusion: A tiered approach-initial screening with FNAC or ZN staining followed by CBNAAT confirmation—provides accurate, feasible, and cost-effective EPTB diagnosis.